A comparative study between the possible protective role of melatonin versus its combination with adipose derived-mesenchymal stem cells on experimentally induced diabetic retinopathy in adult male albino rats (Histological and immunohistochemical study). (4th May 2023) - Reda, Samar; Elsammak, Ghada A; Elsayed, Tamer G; Mostafa, Samar Abdelaziz
ABSTRACT: Diabetes mellitus is a metabolic disorder that can cause numerous ocular issues as well as long-term effects. In our study, we evaluate the effect of melatonin on the diabetic retinal alterations in male albino rats to the effect of melatonin combined with stem cells. 50 adult male rats were equally divided into four groups control, diabetic, melatonin, and melatonin plus stem cells. STZ, 65 mg/kg in phosphate buffered was administered intraperitoneally as a bolus to diabetic group of rats. After inducing diabetes, melatonin (10 mg/kg b.wt./day) was administered orally to the melatonin group for 8 weeks. The stem cell and melatonin group got the same dosage of melatonin as the prior group. They received an intravenous injection of (3?×?106 cell) adipose-derived MSC suspended in phosphate-buffered saline at same time of melatonin ingestion. Animals from all groups had their fundics examined. Following the injection of stem cells, samples of rat retina were collected for light and electron microscopy analyses. H&E and immunohistochemically stained sections revealed a slight improvement in group (III). At the same time, group (IV) results were comparable to those of the control group, which was supported by the findings of an electron microscope. Neovascularization was visible on fundus examination in group (II), whereas it was less noticeable in group (III) and group IV. Melatonin mildly improved the histological structure of the retina in diabetic rats, and when it was combined with adipose-derived MSC, it considerably improved the diabetic alterations.